The Impact of Rice Price and Product Quality on Consumer Purchase Decisions (Systematic Literature Review) - Rika Santi; Indah Nurdiana; Riska Rezievi Anjalina (PT. Hidayat Muda Intelektual, 2025)
This study aims to determine the effect of price and quality of rice products on purchasing decisions. The analysis was conducted using the Systematic Literature Review (SLR) method with a quantitative approach. There were 200 research findings found through the Publish Or Perish (POP) database, but only 20 research articles were considered relevant to the keywords. The results of the study showed that the variables of rice price and product quality were proven to significantly influence consumer purchasing decisions, both directly and partially. Due to its inelastic nature, changes in rice prices can affect food security, but premium rice tends to be preferred over medium rice. Thus, researchers found that there were several studies that quality had a positive effect, while price did not. This shows that customers often prioritize quality over price. The results of this study confirm that in order to support national food security, government policies must be implemented to maintain price stability and improve the quality of rice products.